Challenges of education and learning in the metaverse - Meyzan Briceño, María Amparo (2022)
Education is intimately linked to learning, although both have serious but complementary differences. While education is formative, methodological, rigid, closed or specialized, where the life project is built; learning is flexible and is connected to the acquisition of skills, competencies and abilities that generate personality traits such as autonomy, responsibility, emotional stability, kindness, among others.